2024
DOI: 10.1111/srt.13714
|View full text |Cite
|
Sign up to set email alerts
|

Use of platelet rich plasma for skin rejuvenation

Lam Kar Wai Phoebe,
Kar Wai Alvin Lee,
Lisa Kwin Wah Chan
et al.

Abstract: ObjectivePlatelet‐rich plasma (PRP) is recognized as a safe and effective therapy for regenerative skin healing and rejuvenation, utilizing autologous blood enriched with various growth factors. This review aims to assess the efficacy of PRP treatments for skin rejuvenation.MethodsKeywords such as “platelet‐rich plasma,” “rejuvenation,” “skin aging,” and “wrinkles” were queried on Ovid, PubMed, and MEDLINE to identify pertinent studies on PRP treatment for skin rejuvenation.ResultsAnalysis revealed that PRP tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Facial rejuvenation treatments with PRF aim to improve skin texture, elasticity, and overall appearance. The growth factors in PRF are known to stimulate collagen production, which is crucial in maintaining skin elasticity and strength, thereby potentially reducing wrinkles and improving skin texture [8,9]. Clinical trials and cohort studies have shown promising results in using PRF for facial esthetic improvements, including reducing the appearance of wrinkles and fine lines [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Facial rejuvenation treatments with PRF aim to improve skin texture, elasticity, and overall appearance. The growth factors in PRF are known to stimulate collagen production, which is crucial in maintaining skin elasticity and strength, thereby potentially reducing wrinkles and improving skin texture [8,9]. Clinical trials and cohort studies have shown promising results in using PRF for facial esthetic improvements, including reducing the appearance of wrinkles and fine lines [10,11].…”
Section: Introductionmentioning
confidence: 99%